INFLUENCE OF PUBERTY ON THE ACTIVENESS OF STUDENT LEARNING IN CLASS V MADRASAH IBTIDAIYAH BELITANG SUBDISTRICT EAST OKU COUNTY (Adi Widya: Jurnal Pendidikan Dasar, 2022)
Puberty is the time when individuals experience physical, psychic and maturation changes in the functioning of sexual organs. The problem in this study is whether there is an influence of puberty on the activeness of learning students in class V Madrasah Ibtidaiyah. The research method used in this research is quantitative research with the type of survey. This study uses two places, namely class V MI Bustanul Ulum Wonotirto and MI Islamiyah Sidorahayu located in Belitang sub-district, which is as many as 33 learners. Sampling technique uses systematic sampling techniques with a sample number of 27 learners. The results of the study of the percentage of puberty of class V students were 40.7% high and 40.7% moderate as many as 22 participants. The percentage of learning activity is 55.6% as many as 15 learners in the moderate category. From the results of the hypothesis test obtained that a significant value of 0.00 ≤ 0.05 then Ha was accepted and Ho was rejected, this means that there is a significant influence between puberty on the active learning of students of class V Madrasah Ibtidaiyah Belitang Subdistrict. Explained the percentage of the influence of puberty variable (X) on the student learning activity variable (Y) which is R Square of 0.431. This means that there is an influence of puberty on the active learning of class V students, which is 57% > 43%. Keywords: Puberty, Student Learning Activities.